Respuesta :

Answer:

Step-by-step explanation:

Simplifying

8x + -31 + 5y + 35 + 6x + 3 = 180

Reorder the terms:

-31 + 35 + 3 + 8x + 6x + 5y = 180

Combine like terms: -31 + 35 = 4

4 + 3 + 8x + 6x + 5y = 180

Combine like terms: 4 + 3 = 7

7 + 8x + 6x + 5y = 180

Combine like terms: 8x + 6x = 14x

7 + 14x + 5y = 180

Solving

7 + 14x + 5y = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.

7 + 14x + -7 + 5y = 180 + -7

Reorder the terms:

7 + -7 + 14x + 5y = 180 + -7

Combine like terms: 7 + -7 = 0

0 + 14x + 5y = 180 + -7

14x + 5y = 180 + -7

Combine like terms: 180 + -7 = 173

14x + 5y = 173

Add '-5y' to each side of the equation.

14x + 5y + -5y = 173 + -5y

Combine like terms: 5y + -5y = 0

14x + 0 = 173 + -5y

14x = 173 + -5y

Divide each side by '14'.

x = 12.35714286 + -0.3571428571y

Simplifying

x = 12.35714286 + -0.3571428571y